2017
DOI: 10.1074/jbc.r116.774562
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis for differential type I interferon signaling

Abstract: Type I interferons (IFN-1) are cytokines that affect the expression of thousands of genes, resulting in profound cellular changes. IFN-1 activates the cell by dimerizing its two-receptor chains, IFNAR1 and IFNAR2, which are expressed on all nucleated cells. Despite a similar mode of binding, the different IFN-1s activate a spectrum of activities. The causes for differential activation may stem from differences in IFN-1-binding affinity, duration of binding, number of surface receptors, induction of feedbacks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
191
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(198 citation statements)
references
References 103 publications
(121 reference statements)
4
191
0
3
Order By: Relevance
“…We generated tSNE plots to show genes expression in specific clusters of cells (van der Maaten and Hinton, 2008). IFN-α and IFN-β bind a heterodimeric transmembrane receptor termed the IFN-α receptor (IFNAR), which is composed of IFNAR1 and IFNAR2 subunits (Schreiber, 2017). We observed expression of both Ifnar1 (Interferon receptor 1, IFNR1) and Ifnar2 (Interferon receptor 2, IFNR2) mRNAs with the neuronal marker rbfox3 (NeuN), indicating their presence in neuronal populations in the mouse DRG (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated tSNE plots to show genes expression in specific clusters of cells (van der Maaten and Hinton, 2008). IFN-α and IFN-β bind a heterodimeric transmembrane receptor termed the IFN-α receptor (IFNAR), which is composed of IFNAR1 and IFNAR2 subunits (Schreiber, 2017). We observed expression of both Ifnar1 (Interferon receptor 1, IFNR1) and Ifnar2 (Interferon receptor 2, IFNR2) mRNAs with the neuronal marker rbfox3 (NeuN), indicating their presence in neuronal populations in the mouse DRG (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…From this perspective, an ideal candidate is type I interferons (IFNs) because these cytokines are rapidly induced in a wide variety of cells upon exposure to virus. These IFNs then act via their cognate receptors to induce signaling in target cells (Schreiber, 2017; Barrat et al, 2019). We hypothesized that type I IFNs might act directly on peripheral nociceptors to cause pain.…”
Section: Introductionmentioning
confidence: 99%
“…B,C and http://onlinelibrary.wiley.com/doi/10.1002/hep.29609/suppinfo). Considering that the actions of IFN‐α are closely associated with the cell‐surface receptor concentrations and a much higher number of IFNAR receptors is associated with antiproliferative, rather than antiviral, activity, we further examined the expression of IFNAR1, IFNAR2, TYK2, and JAK1. The results showed that these signaling molecules were expressed highly in HepG2‐NTCP, but at a much lower level in PHH (Fig D), which might contribute to the differential induction pattern of ISGs and antiviral effects.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, both the high expression of conventional EGFR and its phosphorylated form (pEGFR) can be unfavorable prognostic factors for cancer patients. The hyperexpression of pEGFR on salivary gland tumor cells enhanced their migratory activity and promoted lymphogenic metastases and invasion into the lymph nodes [26]. …”
Section: Role Of Changes In Receptor Expression Density In Health Andmentioning
confidence: 99%